Comparison Of Giving Three Types Of Honey On Exudate Weight In The Healing Process Of Acute Wounds In Balb/C Mice - Eko Naning Sofyanita (Journal Of Global Research Publications, 2024)
A wound is an injury where the skin is torn, cut or punctured, or a blunt force trauma causes a contusion. The use of honey as a wound treatment has been widely used, but the comparison of accelerated wound healing using three types of honey originating from Indonesia is not yet known. From the results of the study that on days 1 to 7 the MD-NTT group could reduce exudate weight better than the MD-JW, MD-KLM, and K-MD. The conclusion in this study is that the use of honey originating from NTT can be an alternative to healing acute wounds infected with bacteria.